Optimization of Blast Furnace Throughput Based on Hearth Refractory Lining and Shell Thickness - Ossia, Chinwuba Victor; Shedrack, Mathew Uzoma (Journal of Casting & Materials Engineering, 2021)
Computational analyses were performed to optimize the furnace throughput, steel shell and lining thickness of a blast furnace. The computations were done for measured parameters within the hearth region as this is the vital zone of the furnace with high temperature fluctuations, molten iron, and slag production. The lining materials were namely 62% high alumina (A), carbon composite (B), silicon carbide (C) and graphite bricks (D) with thermal conductivities 2, 12, 120 and 135 W/(m∙K), respectively. It was observed that by varying the refractory lining thickness from 0.2–0.35 m, and furnace inside temperatures from 1873–2073 K, certain optimal conditions could be specified for the furnace under consideration. Silicon carbide and graphite brick linings which have higher thermal conductivities, melting points, good chemical and mechanical wear resistance were observed to be the best hearth lining materials. Due to the high thermal conductivities of these two materials, the hot face temperature levels of the lining materials would be lowered. Amongst the four lining materials employed, silicon carbide and graphite bricks when used with lining cooling systems could optimize the blast furnace for better performance, production, and longer campaigns.